Knowledge management enhancing risk management of agile software development projects using SCRUM (Advances in Knowledge Representation, 2023)
This study aimed to propose a model in which knowledge management enhances risk management in agile software development projects using Scrum taking into consideration the tacit character of knowledge in agile methodologies. This research was developed using the Design Science methodology (DS) and the Design Science Research (DSR), a prescriptive method which proposes the generation of an artifact, in this case, a knowledge management model that enhances risk management in the development of software with Scrum. This research was based on literature review and quantitative analysis of a questionnaire applied to 121 people. The results obtained with the questionnaire showed that all stages of knowledge management can positively impact risk management. In verifying the risks related to the loss of knowledge at the end of the sprints, it was identified that due to the use of knowledge acquired in past experiences, there was an increase of knowledge, not a negative but positive risk. Another result was that would not be necessary a detailed documentation to avoid loss of knowledge at the end of sprints. The created model was validated through a focus group with people who work with agile software project development and, after adjustments, the proposed model was obtained.